Older tourist behavior and marketing tools - Vigolo, Vania (Springer, 2017)
This book provides an in-depth analysis of the older-tourist market, and of the challenges and opportunities created by population ageing from a tourism marketing perspective, by combining a demand-side and a supply-side approach to older tourists. The book is divided into three parts, the first of which defines older tourists and presents a critical review of segmentation approaches. The second part then focuses on the behavior of older tourists in terms of the travel planning process, the use of information and communication technologies for travel purposes, and accommodation choices. The final part analyzes the marketing strategies and operative practices of three tourism companies that focus on the older-adult market. Practical implications for tourism suppliers willing to target older tourists are derived. The book is intended primarily for academics, researchers, and professionals in the tourism and hospitality industry. In addition, it will be useful for students attending advanced tourism and hospitality courses.
Keywords: Tourists.; Older people.; elektronické knihy; electronic books